Concurrent training in Rugby Sevens: Effects of high-intensity interval exercises - Robineau, J.; Lacome, M.; Piscione, J.; Bigard, X.; Babault, N. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To assess the impact of 2 high-intensity interval-training (HIT) programs (short interval vs sprint interval training) on muscle strength and aerobic performances in a concurrent training program in amateur rugby sevens players.